Characterization and Genomic Analysis of Marinobacter Phage vB_MalS-PS3, Representing a New Lambda-Like Temperate Siphoviral Genus Infecting Algae-Associated Bacteria - Liu, Yundan; Zheng, Kaiyang; Liu, Baohong; Liang, Yantao; You, Siyuan; Zhang, Wenjing; Zhang, Xinran; Jie, Yaqi; Shao, Hongbing; Jiang, Yong; Guo, Cui; He, Hui; et al. (Frontiers in Microbiology, 2021)
Marinobacter is the abundant and important algal-associated and hydrocarbon biodegradation bacteria in the ocean. However, little knowledge about their phages has been reported. Here, a novel siphovirus, vB_MalS-PS3, infecting Marinobacter algicola DG893(T), was isolated from the surface waters of the western Pacific Ocean. Transmission electron microscopy indicated that vB_MalS-PS3 has the morphology of siphoviruses. VB_MAlS-PS3 was stable from -20 to 55℃, and with the latent and rise periods of about 80 min and 10 min, respectively. The genome sequence of VB_MAlS-PS3 contains a linear, double-strand 42,168-bp DNA molecule with a G+C content of 56.23% and 54 putative open reading frames. Nineteen conserved domains were predicted by BLASTp in NCBI. We found that vB_MalS-PS3 represent an understudied viral group with only one known isolate. The phylogenetic tree based on the amino acid sequences of whole genomes revealed that vB_MalS-PS3 has a distant evolutionary relationship with other siphoviruses, and can be grouped into a novel viral genus cluster with six uncultured assembled viral genomes from metagenomics, named here as Marinovirus. This study of the Marinobacter phage vB_MAlS-PS3 genome enriched the genetic database of marine bacteriophages, in addition, will provide useful information for further research on the interaction between Marinobacter phages and their hosts, and their relationship with hydrocarbon biodegradation in the ocean.